Provisional checklist of the Tettigonioidea (Insecta: Orthoptera) from São Tomé & Príncipe with taxonomic remarks, bioacoustical data and the description of new taxa - Heller, Klaus-Gerhard (Zootaxa, 2019)
The state São Tomé and Príncipe consists of two separated oceanic archipelagos situated in the Gulf of Guinea (West Central Africa). Except of a first survey on São Tomé in the 19th century, its Orthoptera fauna has never been studied systematically. Here a list of all tettigonioid species which have been recorded from the islands is presented together with information about the bioacoustics and biology of some species. Each archipelago harbours nine species, but only two species are found in both parts of the country. Two species and one subgenus are described as new: Adapantus (Adapantus) excavatus sp. nov., Brachyamytta bombomensis sp. nov., Neoadapantus subg. nov. The following nomenclatural changes had to be done: Corycoides greeffi (Krauss, 1890) becomes new synonym of Corycoides paradoxus (Bolivar, 1890), Xiphidion guineensis Redtenbacher, 1891, Xiphidion africanum Redtenbacher, 1891 and Conocephalus inequalis Uvarov, 1928 become new synonyms of Conocephalus iris Serville, 1838. The species list of Conocephalus, subgenus Conocephalus, is revised. Additionally the known tettigonioids of Annobón (Equatorial Guinea) are listed (4 species).